Report on: Mapping natural resource (soil, weather, agro-biodiversity) to identify hot-spots and suitable areas in Sudan - Atassi, Layal; Devkota, Krishna; Devkota Wasti, Mina Kumari (2024)
This report summarizes the trend in average temperature, precipitation over time and space from different region in Sudan. Also, it includes identification of hot spots for various climatic and soil parameters such as long-term rainfall patterns, rainfall variability, areas prone to drought, as well as average, maximum, and minimum temperatures essential for wheat cultivation. Furthermore, parameters related to soil fertility, such as texture, soil organic carbon content, slope/elevation, and soil salinity, are considered. Soil-water resources, including groundwater availability, dam locations, and soil displacement by water, are also evaluated. Vegetation indices such as NDVI (Normalized Difference Vegetation Index) and ground cover are mapped for different region in Sudan.